Gambaran pola asupan makanan pada remaja di Kabupaten Bolaang Mongondow Utara - Mokoginta, Farah S.; Budiarso, Fona; Manampiring, Aaltje E. (eBiomedik, 2016)
Abstract: Food pattern is an important criteria that affecting the nutrition and to fulfill the need of balanced nutrition. Adolescents are often indicated as vulnerable because of their massive growth and development as well as their highly needs of energy to do various of physical activities. The insufficiency of food pattern can easily affecting due to their imbalanced growth and development, and increase higher risk prior to many chronic diseases regarding their adultery life. The importance of balanced food pattern and nutrition intake in adolescence and there has been no amount of research applied for North Bolaang Mongondow province attract the writer to do this research. The main purpose of this research is to know the pattern of food and nutrition consumption in adolescent. This research is a descriptive study with the design of cross sectional. The results showed the majority of food consumed by adolescents are rice (90%), fishes (77,5%), tofu (47,5%), water spinach (57,5%), banana (32,5%), milk (47,5%), bread (47,5%), and cola-cola (30%) for >1/day frequent. The amount of energy consumption is severely insufficient (97,5%), carbohydrate consumption is <70% RDA (95%), protein is <70% RDA (77,5%), and total fat is <70% RDA (77,5%). Conclusion: The food pattern in adolescent commonly has less various of menu where the average of frequency is >1/day with minimum amount of food and incomplete of consumption each of time.Keywords: food pattern, food consumption, nutrition, adolescentÂ Abstrak: Pola makan merupakan kebiasaan penting yang dapat mempengaruhi keadaan gizi dan untuk memenuhi kebutuhan gizi seimbang. Usia remaja adalah usia rentan gizi karena tumbuh kembang yang pesat dan dibutuhkan energi yang cukup untuk melakukan beragam aktivitas fisik. Jika pola asupan buruk, akan berdampak pada pertumbuhan dan perkembangan yang tidak optimal, serta lebih rentan terhadap penyakit-penyakit kronis di masa dewasa. Pentingnya pola asupan makan yang seimbang pada remaja serta belum adanya penelitian yang dilakukan di daerah Bolaang Mongondow Utara membuat penulis tertarik untuk melakukan penelitian ini. Tujuan umum penelitian ini adalah untuk mengetahui gambaran pola asupan makanan pada remaja di Kabupaten Bolaang Mongondow Utara. Jenis penelitian ini bersifat deskriptif dengan menggunakan desain potong lintang (cross sectional). Hasil penelitian ini menunjukan bahwa kategori terbanyak yang dikonsumsi adalah beras(90%), ikan segar (77,5%), tahu (47,5%), kangkung (57,5%), pisang (32,5%), susu (47,5%), roti (47,5%), dan cola-cola (30%) untuk frekuensi >1x/hari. Tingkat kecukupan energi didapati sangat kurang (97,5%), kecukupan karbohidrat <70% AKG (95%), protein <70% AKG (77,5%), dan lemak <70% AKG (77,5%). Simpulan: Pola makan remaja umumnya kurang bervariasi dengan frekuensi rata-rata >1x/hari namun dengan jumlah yang sedikit dan dikonsumsi tidak lengkap tiap kali makan. Tingkat kecukupan gizi remaja <70% AKG menandakan bahwa asupan energi dari sumber karbohidrat, protein, lemak sangat kurang. Kata kunci: pola makan, pola konsumsi, nutrisi, asupan gizi, remaja.